Optimization design for foam-filled double cylindrical tubes under multiple lateral impacts. (December 2018) - Jiang, Ping; Wang, Qidong; Yin, Andong; Hu, Jinfang; Gu, Xianguang
Nowadays, thin-walled foam-filled structures have already been excessively used in automobile industry due to the superior energy absorption capacity and relatively light weight. The components in vehicle probably subject to lateral impact at any position in practice; however, most of the previous literature focused only on the bending behavior of structures under lateral impact at the mid-span. In this study, a hybrid structure of the structural epoxy foam Terocore ® and two cylindrical tubes is comprehensively investigated under various lateral impact positions. The finite element model of the hybrid structure is established and then validated by the experimental results. From a numerical study, several design parameters, including the thicknesses of outer and inner tubes, the diameters of inner tubes, and the foam densities, are explored to exhibit great effects on the bending resistance of the hybrid structure. To find the optimal designs of the hybrid structure under different load cases, a system methodology, which is constructed by optimal Latin hypercube sampling, radial basis function model and multi-objective particle swarm optimization algorithm, is implemented. Compared with the original design, the optimization designs of different load cases perform better bending resistance, namely, higher specific energy absorption and lower peak crushing force. Therefore, the optimal hybrid structure can be considered as a practical candidate for energy absorbing under lateral impact.